FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS DAN OBYEKTIVITAS AUDITOR PADA KANTOR AKUNTAN PUBLIK LOMBOK TIMUR - Lisa Mariantini; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This research was conducted to determine the factors that can affect the integrity and objectivity of auditors working at the East Lombok Public Accounting Firm. Which of these factors are Auditor Quality, Audit Fee, Audit Period. The sample in this study is an auditor who works in a public accounting firm. The type of research in the preparation of this thesis is correlational research. The analytical method used is Multiple Linear Regression with SPSS 23 Software For Windows. Based on the results of research and discussions that have been carried out, it can be concluded that Auditor Quality has no significant effect on Auditor Integrity and Objectivity, Audit Fee has a significant effect on Auditor Integrity and Objectivity, and Audit Period has a significant effect on Auditor Integrity and Objectivity.Keywords: Integrity, Objectivity, Auditor Quality, Audit Fee, Audit Period.